Effect of tailored density profiles on the stability of imploding Z-pinches at microsecond rise time megaampere currents. (6th December 2021) - Cherdizov, R K; Baksht, R B; Kokshenev, V A; Oreshkin, V I; Rousskikh, A G; Shishlov, A V; Shmelev, D L; Zhigalin, A S
Abstract: To study the effect of the radial density profile of the material of a metal-plasma Z-pinch load on the development of magneto-Rayleigh–Taylor (MRT) instabilities, experiments have been performed at the Institute of High Current Electronics with the GIT-12 generator which produces microsecond rise time megaampere currents. The Z-pinch load was an aluminum plasma jet (PJ) with an outer plasma shell. This configuration leads to the formation of a uniform current sheath in a Z-pinch load upon application of a high-voltage pulse. It was successfully used in experiments with hybrid deuterium gas-puffs (Klir et al 2020 New J. Phys. 22 103036). The initial density profiles of the Z-pinch loads were estimated from the pinch current and voltage waveforms using the zero-dimensional 'snowplow' model, and they were verified by simulating the expansion of the PJ formed by a vacuum arc using a two-dimensional quasi-neutral hybrid model (Shmelev et al 2020 Phys. Plasmas 27 092708). Two Z-pinch load configurations were used in the experiments. The first configuration provided tailored load density profiles, which could be described as ρ ( r ) ≍ 1/ r ^ s for s > 2. In this case, MRT instabilities were suppressed and thus a K-shell radiation yield of 11 kJ cm −1 and a peak power of 0.67 TW cm −1 could be attained at a current of about 3 MA. For the second configuration, the radial density profiles were intentionally changed using a reflector. This led to the appearance of a notch in the density profiles at radii of 1–3 cm from the pinch axis and to magnetohydrodynamic instabilities at the final implosion stage. As a result, the K-shell radiation yield more than halved and the power decreased to 0.15 TW cm −1 at a current of about 3.5 MA.